Kindergarten science fun-filled activities (Noida Om Books, 2021)
The smart scholars series is a collection of fun, activity-based workbooks that encourage your child to learn through many interesting activities. The 10 books in grade 3 cover exercises that range from punctuation, parts of Speech to mathematical operations, equations Measurement, and Symmetry. It also covers skills to sharpen reading Comprehension. These concepts are presented with lucid, visual examples, giving the child ample scope to practice. With more than 30 colourful pages of amazing activities, this series is a complete package that will turn your child's learning hours fly by!.
Keywords: Elementary School education